Electron-Ion Mixed Conduction of Nd0.6Sr0.4FeO3 Cathode Electrode Thin Film for Solid Oxide Fuel Cell. (11th January 2017) - Namiki, Wataru; Takayanagi, Makoto; Furuichi, Shoto; Tsuchiya, Takashi; Minohara, Makoto; Kobayashi, Masaki; Horiba, Koji; Kumigashira, Hiroshi; Higuchi, Tohru
Abstract : Nd0.6 Sr0.4 FeO3 (NSFO) thin films with various thicknesses have been deposited on Al2 O3 (0001) substrates by RF magnetron sputtering. The lattice constant decreases with increasing film thickness. The electrical conductivity is higher than that of the bulk crystal. The conductivity at 500˚C does not depend on the oxygen gas partial pressure. The value of band gap corresponds to the activation energy calculated from Arrhenius plots. These results indicate that NSFO thin film has the high electron conduction in addition to oxygen–ion conduction at 500˚C.